IRS Spectroscopy and Multi-wavelength Study of Luminous Star-forming Galaxies at z~1.9 - Huang, J; Faber, S; Daddi, E; Laird, E; Lai, K; Omont, A; Wu, Y; Younger, J; Bundy, K; Cattaneo, A; Chapman, S; Conselice, C; et al. (2009)
We analyze a sample of galaxies chosen to have F24>0.5 mJy and satisfy a certain IRAC color criterion. IRS spectra yield redshifts, spectral types, and PAH luminosities, to which we add multi-wavelength broadband photometry. Stellar population modeling and IRS spectra together demonstrate that the double criteria used to select this sample have efficiently isolated massive star-forming galaxies at z~1.9. This is the first starburst-dominated ULIRG sample at high redshift with total infrared luminosity measured directly from FIR and millimeter photometry, and as such gives us the first accurate view of broadband SEDs for starburst galaxies at extremely high luminosity and at all wavelengths. Similar broadband data are assembled for three other galaxy samples -- local starburst galaxies, local AGN/ULIRGS, and a second 24mu-luminous z~1.9 sample dominated by AGN. L(PAH)/L(IR) for the new z~1.9 starburst sample is the highest ever seen, some three times higher than in local starbursts, whereas in AGNs this ratio is depressed below the starburst trend, often severely. Several pieces of evidence imply that AGNs exist in this starburst dominated sample, except two of which even host very strong AGN, while they still have very strong PAH emission. The ACS images show most objects have very extended morphologies in the rest-frame UV band, thus extended distribution of PAH molecules. Such an extended distribution prevents further destruction PAH molecules by central AGNs. We conclude that objects in this sample are ULIRGs powered mainly by starburst; and the total infrared luminosity density contributed by this type of objects is 0.9-2.6x 10^7 Lsol/Mpc^3.